Primitivos Somos Nós - Jorge, Vítor Oliveira (Trabalhos de Antropologia e Etnologia, 2020)
a brief reflection on the Western invention of the pejorative idea of "primitivism" applied to exotic societies, and a suggestion that, with neoliberal capitalist development, it was the West that became somewhat savage and that such new kind of barbarism expanded to everywhere.